What Drives the Urban Wage Premium? Evidence along the Wage Distribution - Alessia Matano; Paolo Naticchioni (Institute for the Study of Labor (IZA), 2013)
This paper aims at disentangling the role played by different explanations on the urban wage premium along the wage distribution. We analyze the wage dynamics of migrants from lower to higher density areas in Italy, using quantile regressions and individual data. The results show that unskilled workers benefit more from a wage premium accruing over time, while skilled workers enjoy a wage premium when they migrate as well as a wage increase over time. Further, we find that for unskilled workers the wage growth over time is mainly due to human capital accumulation, consistently with the learning hypothesis, while for skilled workers it is the coordination hypothesis that matters.
Keywords: J31; J61; R23; 330; urban wage premium; human capital; spatial sorting; wage distribution; quantile fixed effects